НТР, рабочий класс, интеллигенция - Бляхман Леонид Соломонович (Политиздат, 1973)
Экземпляры: КХ (20121012) / Инвентарный номер: 570768 / Цена: 0.74 / Сис.шифр: 32С / Авт.знак: Б 71 / ГРНТИ: 11 / ББК: 66